Perbedaan Serotonin Plasma dan Kortisol Saliva terhadap Gejala Depresi pada Pasien Pasca Sindrom Koroner Akut - Firmansyah, Irman; Shatri, Hamzah; Putranto, Rudi; Ardani, Yanuar; Ginanjar, Eka; koesnoe, sukamto; Rizka, Aulia; Isbagio, Harry; Yunir, Em (UI Scholars Hub, 2023)
Introduction. Psychological disorders are closely associated with hormonal factors, including cortisol and serotonin. In patients with acute coronary syndrome (ACS), autonomic dysfunction and dysregulation of the hypothalamic-pituitaryadrenal (HPA) axis can occur, leading to an increase in cortisol levels that may worsen the prognosis of ACS patients. Therefore, it is important to understand the hormonal impact, namely cortisol and serotonin levels, on depressive symptoms, which will be examined in this study. Methods. This was a cross-sectional study to determine the impact of cortisol and serotonin in the incidence of depression in post-treatment ACS patients at the ICCU RSUPN dr. Cipto Mangunkusumo, Jakarta. Data collection from patients meeting the inclusion criteria was carried out 10-14 days post-treatment through interviews, HADS questionnaire completion, physical examinations, and laboratory tests. The Mann-Whitney test was used to examine the differences between serotonin and salivary cortisol levels in patients with and without depression. Results. Among the 73 ACS patients included in this study, the average age was 57.53 (9.97) years, with 68.5% was male. Posttreatment depression was observed in 15.1% of subjects. The median serotonin levels were lower in patients with depression [175 (147 – 227.64) ng/mL vs. 189.31 (152.87-235.44) ng/mL], while cortisol levels were higher in patients with depression [3.09 (1.46-6.26) ng/mL vs. 2.15 (0.92-3.91) ng/mL]. However, the statistical analysis showed no significant differences between plasma serotonin and depression (p=0.482) or saliva cortisol and depression (p=0.275). Conclusions. There were no significant differences in cortisol and serotonin levels concerning depressive symptoms among post-acute coronary syndrome patients. Nevertheless, this study holds clinical importance due to the observed lower plasma serotonin levels and higher saliva cortisol levels in ACS patients with depression.